Evaluation of wind energy potential over offshore areas in Vietnam - Mai, Van Khiem; Nguyen, Ba Thuy; Tran, Viet Lien; Vu, Van Thang; Du, Duc Tien; Pham, Thanh Hoa Thi; Hole, Lars Rober (Vietnam Journal of Marine Science and Technology, 2025)
The study evaluates the technical potential of offshore wind energy in Vietnam based on a 30-year dataset (1991–2020) with a spatial resolution of up to 3 km. The offshore wind energy potential was determined at a height of 100 meters (above sea level) for Vietnam’s exclusive economic zone and was classified into shallow waters (depths below 50 meters) and deep waters (50–1000 meters) and by month of the year. The results of the technical wind energy potential calculation differ significantly from some previous studies, particularly from the World Bank’s report published in 2022. This difference is due to the expanded spatial coverage of the current study and a larger area with wind speeds greater than or equal to 7 ms-1. Additionally, detailed information on the temporal variability of wind energy density and technical wind energy potential was analyzed, showing large fluctuations between months, with the highest potential occurring in the winter months and the lowest in spring. The results not only contribute to scientific knowledge about renewable energy but also provide reference information for marine spatial planning, with applications in activities related to the development of offshore wind energy in Vietnam.